The Role of DPRD in the Supervision Function of the Implementation of the North Sumatra Province APBD - Muhammad Adli Azrai; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
Supervision of the budget is part of the main duties of the members of the council who act as representatives of the people, therefore all revenues from the people that are intended for development must be monitored so that there is no fraud. This study aims to analyze the role of DPRD in carrying out their duties in the supervisory function of the implementation of the North Sumatra Province APBD and to find out how the stages and procedures for budgeting and accountability reports are. To achieve the research objectives, the researcher used a qualitative descriptive research method with a study of literature related to the topic of this research. The results of the study found that in the implementation of budget oversight there were still some notes and corrections to members of the DPRD of North Sumatra Province, including being less effective in coordinating and communicating supervision of their members, and unable to direct their wishes to the APBD proposal according to regional content when obtaining information from community leaders. . But from the other side there is good news that there is an increase in the performance results achieved. The supervision carried out on the budget consists of supervision during the preparation process, implementation to the accountability report stage.